The Effect of Corn (Zea mays) Cob Extract on the Growth of Bifidobacteria - Sejati, Ribka Ananda; Ariestanti, Catarina Aprilia; Amarantini, Charis (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2023)
Corncob is a source of dietary fiber, contains xylan polysaccharides (12.4%–31.94%), and is classified as the highest xylan-producing source compared to other agricultural wastes. Human digestive enzymes cannot degrade xylan but can be enzymatically degraded by lactic acid bacteria (LAB) through fermentation. This research aimed to evaluate the effect of corncob extract on the growth of Bifidobacterium. Corncob extract is obtained through alkaline extraction. The growth of Bifidobacterium bifidum FNCC 0462 and Bifidobacterium longum FNCC 0463 was observed through in vitro fermentation for 48 h using the total plate count (TPC) method. Bifidobacterium bifidum FNCC 0462 showed the ability to ferment corn cob extract for 48 h of fermentation with the highest growth at 8 h of fermentation (4,08 log10 CFU/mL) while B. longum FNCC 0463 was able to grow up to 16 h of fermentation only. The results indicated that corncob extract could support B. bifidum FNCC 0462 growth.